2019
DOI: 10.1155/2019/8628027
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord-Derived Mesenchymal Stem Cell Therapy Ameliorates Nonalcoholic Fatty Liver Disease in Obese Type 2 Diabetic Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is increasingly common among patients with type 2 diabetes mellitus (T2DM). The two conditions can act synergistically to produce adverse outcomes. However, the therapeutic options for patients with NAFLD and T2DM are currently limited. Human umbilical cord-derived mesenchymal stem cells (UC-MSCs) have shown therapeutic potential for diabetes and hepatic disorders such as liver cirrhosis and fulminant hepatic failure. The present study is aimed at investigating the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…We observed that not only did the liver and adipose MSC-CM therapy have apparent improvement in levels of blood glucose, HbA1c, and AGEs but also the enhanced lipid panel (cholesterol, TG, LDL, HDL, and total lipids); renal function (urea, uric acid, creatinine, and total protein); liver function (AST, ALT, ALP, bilirubin, and albumin); CPK; C-peptide; HO-1; inflammatory markers including IL-6, TNF- α , and CRP; growth factors (liver and serum IGF-1); amylase; histopathological changes; pancreatic cell oxidative stress; and antioxidant markers (MDA, GSH, ROS, CAT, SOD, HO-1, and XO) toward the normal levels consequently reduce DM complications. These results are in agreement with the previous findings in [ 43 , 44 ]. Furthermore, the histopathological examination showed regeneration of β cells with the near-normal pancreatic islet architecture and a decrease in the necrotic score as shown in Figures 2(d) – 2(f) , which approved the therapeutic effect of both liver and adipose MSC-CM therapies with significant improvement in the case of liver MSC-CM than adipose MSC-CM therapy.…”
Section: Discussionsupporting
confidence: 94%
“…We observed that not only did the liver and adipose MSC-CM therapy have apparent improvement in levels of blood glucose, HbA1c, and AGEs but also the enhanced lipid panel (cholesterol, TG, LDL, HDL, and total lipids); renal function (urea, uric acid, creatinine, and total protein); liver function (AST, ALT, ALP, bilirubin, and albumin); CPK; C-peptide; HO-1; inflammatory markers including IL-6, TNF- α , and CRP; growth factors (liver and serum IGF-1); amylase; histopathological changes; pancreatic cell oxidative stress; and antioxidant markers (MDA, GSH, ROS, CAT, SOD, HO-1, and XO) toward the normal levels consequently reduce DM complications. These results are in agreement with the previous findings in [ 43 , 44 ]. Furthermore, the histopathological examination showed regeneration of β cells with the near-normal pancreatic islet architecture and a decrease in the necrotic score as shown in Figures 2(d) – 2(f) , which approved the therapeutic effect of both liver and adipose MSC-CM therapies with significant improvement in the case of liver MSC-CM than adipose MSC-CM therapy.…”
Section: Discussionsupporting
confidence: 94%
“…diseases [30][31][32]. MSCs can be derived from different sources, such as umbilical cord, bone marrow, adipose tissue, skeletal muscle, liver, lung, and dermal tissues, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy has become an attractive therapeutic strategy for various types of diseases [17][18][19][20], and it has achieved certain curative effects in induction therapy in patients with SLE [13]. The purpose of this study was to evaluate the efficacy of MSCs in the treatment of SLE by meta-analysis.…”
Section: Introductionmentioning
confidence: 99%